Frequency and efficiency of putting the ball into play from the side in modern football - Dosic, N. (Sports Science and Health, 2014)
The study attempts to elucidatea part of the structure of competitive football activities and efficiency of the one "interruption of the game." The paper topic is the frequency and effectiveness of putting the ball into play from the side. The paper aims to establish the existence of possible differences in the frequency and efficiency of putting the ball into play from the side at the matches of finalists and semi-finalists of the World Championship in 2010. Out of 255 times the ball was put into play from the side in the so-called "opponent`s" half of the field, one goal was scored in the continuation of action after the ball was put into play from the side. By using the Kruskall Wallis test between the four best ranked national teams of the World Championship in 2010, there were statistically significant differences in putting the ball into play from the side as a result of ball throw into the opponent's box (p = 0.003) and by the shot of the ball at the opponent`s goal, where the ball went near or over the goal or a goalkeeper caught or punched the ball (p = 0.009).